Efektifitas Pengembangan Digital Health Aplikasi SEHATI (Sehat untuk Buah Hati) terhadap Pengetahuan dan Motivasi Ibu Hamil dalam Melakukan Pemeriksaan Triple Eliminasi - Ariani, Antri; Sugiharti, Ina; Maharani, Elsa Fitria; Regita, Ghina (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The development of the digital health application SEHATI (Healthy for Children) aims to increase the knowledge and motivation of pregnant women in undergoing triple elimination examinations, namely HIV, syphilis and hepatitis B screening. This research uses a quasi-experiment method with a one-group pretest-posttest design . A total of 30 pregnant women who had not undergone triple elimination examination at the Rancaekek Community Health Center participated in this research. The intervention is provided through the Android-based SEHATI application which is designed to convey information related to triple elimination screening. The research results show the effectiveness of the SEHATI application in increasing knowledge and motivation of pregnant women regarding triple elimination examinations.